Translation and cross-cultural adaptation of a Nepali version of the Dutch Participation and Activity Inventory for Children and Youth (PAI - CY) with visual impairment - Srijana Adhikari; Ellen Bernadette Maria Elsman; Ruth Marie Antoinette van Nispen; Fleur van Rens; Radhika Upreti Oli; Suman S. Thapa; Gerardus Hermanus Maria Bartholomeus van Rens (SpringerOpen, 2021)
Abstract Background Visual impairment is an important cause of disability in children. There is a lack of information on rehabilitation needs and low vision support services for children with visual impairment in Nepal. This is a pilot study designed to translate, culturally adapt and pre-test the Dutch version of the Participation and Activity Inventory for Children and Youth (PAI-CY) with visual impairment aged 7-17 years to develop a Nepali version. Questionnaires (PAI-CY versions for 7-12 and 13-17 years) were translated using standardized methods and were culturally adapted by a panel of experts. They were pretested to evaluate comprehensibility and relevance among six children with visual impairment and blindness. Finally, participants completed a questionnaire evaluation form. Results The translation and cultural adaptation process resulted in the adaptation of nine items to make them suitable for Nepali culture. Most children had comprehensibility problems with some specific items because of vocabulary, sentence structure and the composition of items. Most of the children were satisfied with the questionnaires. Conclusion The study resulted in the development of a Nepali version of the PAI-CY. We worked with a small group of content experts and a small but representative sample of children which allowed us to use rigorous translation procedures to address language and cultural differences. A population based study has been planned to investigate the psychometric properties of these questionnaires.